Comparison of Cancer Diagnoses Between the US Solid Organ Transplant Registry and Linked Central Cancer Registries. Issue 10 (12th May 2016) - Yanik, E. L.; Nogueira, L. M.; Koch, L.; Copeland, G.; Lynch, C. F.; Pawlish, K. S.; Finch, J. L.; Kahn, A. R.; Hernandez, B. Y.; Segev, D. L.; Pfeiffer, R. M.; Snyder, J. J.; et al.
Abstract : US transplant centers are required to report cancers in transplant recipients to the transplant network. The accuracy and completeness of these data, collected in the Scientific Registry of Transplant Recipients (SRTR), are unknown. We compared diagnoses in the SRTR and 15 linked cancer registries for colorectal, liver, lung, breast, prostate and kidney cancers; melanoma; and non‐Hodgkin lymphoma (NHL). Among 187 384 transplants, 9323 cancers were documented in the SRTR or cancer registries. Only 36.8% of cancers were in both, with 47.5% and 15.7% of cases additionally documented solely in cancer registries or the SRTR, respectively. Agreement between the SRTR and cancer registries varied (kappa = 0.28 for liver cancer and kappa = 0.52–0.66 for lung, prostate, kidney, colorectum, and breast cancers). Upon evaluation, some NHLs documented only in cancer registries were identified in the SRTR as another type of posttransplant lymphoproliferative disorder. Some SRTR‐only cases were explained by miscoding (colorectal cancer instead of anal cancer, metastases as lung or liver cancers) or missed matches with cancer registries, partly due to recipients' outmigration from catchment areas. Estimated sensitivity for identifying cancer was 52.5% for the SRTR and 84.3% for cancer registries. In conclusion, SRTR cancer data are substantially incomplete, limiting their usefulness for surveillance and research. Abstract : Through a comparison of data from the United States solid organ transplant registry and multiple linked cancer registries, the authors demonstrate that the transplant registry is missing a substantial fraction of cancer diagnoses in transplant recipients, highlighting incomplete ascertainment and/or reporting of cancer diagnoses by transplant centers.